(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-4-10-21 Abstract. The article is devoted to the study of Slavic-Germanic linguistic relations. The research material is oikonyms of Slavic origin in the German language. Based on the cognitiveevolutionary approach to the formation of the corresponding units, this attempt is aimed to reflect the evolution of the impact of Slavic linguistic phenomena on the verbal thinking of Germans and the cultural perception of the geographical reality. This approach cannot cover all the features of cultural and historical types of thinking. The analysis confirms, the study of oikonyms allows us to highlight the cognitive features of their formation and stimulates research in the field of knowledge of the role of the Slavic factor in the history of two cultures, based on the principles of historical justice and interaction of Slavic and Germanic peoples throughout the centuries-old history of cohabitation on the territory of Europe. The novelty of the work lies in the development of the author’s research model. The objectives include the classification of a numerous corpus of examples, indicating the date of fixation of the form of a given oikonym in written sources and drawing conclusions about the main methods of verbalization of oikonyms in various cognitive spheres influenced by Slavic languages in the 10th-12th centuries. The analysis allows us to conclude that two-thirds of oikonyms of the Slavic origin are formed according to the model of an anthroponym + a patronymic suffix, denoting the descendants of a person. Among other things, place names are represented by derivatives formed using the suffixes -ane, -ow, -au, -(i)n, -ici or - ovici. The cognitive areas on the basis of which cultural and historical perception and understanding of geographical realities occur include “water basin”, “relief”, “landscape”, “soil”, “flora and fauna”, etc.. Key words: oikonyms, substrate, Slavic-Germanic linguistic relations, word-formation element, modeling, conceptual analysis, types of thinking